Metacognition in musical practices: two studies with beginner and expert Brazilian musicians - Araújo, Rosane Cardoso de; Ferronato, Rafael Stefanichen; Veloso, Flávio Denis Dias (Frontiers in Psychology, 2024)
Metacognition is essential in the musical learning process as it involves understanding the purpose of each task, its planning, execution and evaluation. Considering the relevance of metacognitive processes, our objective in this study was to investigate how expert and beginner musicians manifest and verbalize their metacognitive processes in the context of preparing repertoire for a performance. The method used was a multi-case study carried out in two different contexts: with the five members of a brass quintet made up of professional musicians and with three beginner university violin students. The results obtained indicated that even at different levels of expertise, metacognitive processes were present in the musical practices of participants in the two contexts investigated. It was found that in both cases time management is a component of the preparation process in metacognitive regulation, however, for the beginner violinists in our sample it was a significantly more complex task than for the professional brass players. Regarding the learning monitoring and evaluation processes, it was possible to verify that beginner instrumentalists as well as professional musicians used declarative, conditional and procedural knowledge to carry out and reflect on their musical practices. These results have implications for both the individual and collective study process and for teaching processes. It is also observed that reflective thinking must accompany the processes of individual and collective interpretative-musical practices, considering that the musical results desired by musicians are related to the quality of cognitive, behavioral, affective and motivational undertakings pertinent to control and regulation of metacognitive processes.